(untitled) (Global Journal of Human-Social Science, 2024)
This literature review explores the impact of elearning on the professional development of university teachers in Morocco Through a analysis of existing studies this work reveals that e-learning offers an unprecedented opportunity for the modernization of higher education providing teachers with tools to enrich their practices and facilitating access to training This review highlights the importance of the training and continuous professional development of teachers for the successful integration of e-learning It is crucial to provide teachers with the necessary resources including access to technology digital skills training and teaching support to fully exploit the potential of e-learning Faced with the challenges identified this article calls for future research to empirically assess the impact of e-learning on the professional development of teachers and to explore strategies for optimizing its use in the Moroccan academic context